Effect of Peer Influence and Self-Reflection on Scaffolded Out-of-Class Activity Administered Using a Mobile Application - Muztaba Fuad; Monika Akbar (MDPI AG, 2022)
Student engagement with out-of-class activities is becoming more difficult as students spend fewer hours outside the classroom studying the content. This research developed a mobile educational platform, Dysgu, to provide students with an optimal learning experience outside of the classroom. Dysgu includes social networking and gamification features to increase student engagement. The platform offers interactive auto-graded assessments to help students practice concepts and take tests. Students can see their scores and a summary of the performance of the rest of the class. We used Dysgu for multiple out-of-class activities at two universities with different student demographics for two semesters. The data shows that students obtain better grades when using Dysgu. We also saw more on-time or ahead-of-time submissions with Dysgu. Survey responses indicated several Dysgu features which students found helpful. We conclude that digital educational platforms should consider features to support scaffolding to master the concept, peer influence to keep students engaged, self-reflection to foster critical thinking, and easy adaption of the platform to reduce faculty workload and improve students' acceptance of the system.